PENERAPAN METODE QIRA’ATI UNTUK MENINGKATKAN KUALITAS BACAAN AL-QUR’AN DI TPQ ZAHROTUL MUBTADI’IN PONDOKPESANTREN RAUDLTAUL MUBTADI’IN MAJALENGKA - Adib Amrullah; Salman Alfarisi, Rizki Ferawati, Syifa Hana Musyaffa, Lala Putri Maretha, Ahmad Fu’adin (CV. ADIBA AISHA AMIRA, 2023)
TPQ Zahrotul Mubtadi'in Majalengka uses the Qiro'ati method in understanding Al- Qur'an learning. The application of the Qiro'ati Method uses the technique of reading it directly without any pause in the reading and the reading must also be precise, correct, smooth and also tartil in accordance with the laws of recitation. The title of this research journal is